The patient portal and abnormal test results: An exploratory study of patient experiences - Traber Giardina (The Beryl Institute, 2015)
Many health care institutions are implementing patient portals that allow patients to track and maintain their personal health information, mostly in response to the Health Information Technology for Economic and Clinical Health Act requirements. Test results review is an area of high interest to patients and provides an opportunity to foster their involvement in preventing abnormal test results from being overlooked, a common patient safety concern. However, little is known about how patients engage with portals to review abnormal results and which strategies could facilitate that interaction in order to ensure safe follow-up on abnormalities. The objective of this qualitative study was to explore patients’ experiences related to abnormal test result notifications through patient portals. The authors conducted semi-structured telephone interviews with 13 participants, patients and primary caregivers, between February 2014 and October 2014. Using content analysis, the authors explored patient experiences accessing abnormal test results through their portals. Respondents strongly favored access to all types of abnormal test results, but they raised several concerns including need for more timely notification and not being able to interpret the exact relevance of the result. Respondents’ personal experiences with physicians, test result notification, and the portal heavily influenced respondents’ notification preferences. Patient experiences with portals could be improved by development of strategies to help patients understand and manage the information received. These findings suggest important considerations for health professionals and institutions aiming to better engage patients in follow-up of their test results.